What Your Tweets Tell Us About You: Identity, Ownership and Privacy of Twitter Data - Heather Small; Kristine Kasianovitz; Ronald Blanford; Ina Celaya (International Journal of Digital Curation, 2012)
Social networking sites and other social media have enabled new forms of collaborative communication and participation for users, and created additional value as rich data sets for research. Research based on accessing, mining, and analyzing social media data has risen steadily over the last several years and is increasingly multidisciplinary; researchers from the social sciences, humanities, computer science and other domains have used social media data as the basis of their studies. The broad use of this form of data has implications for how curators address preservation, access and reuse for an audience with divergent disciplinary norms related to privacy, ownership, authenticity and reliability.